2016
DOI: 10.12659/msm.896297
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Genetic Variants of the NOTCH3 Gene and Ischemic Stroke Risk

Abstract: BackgroundIschemic stroke (IS) is a leading cause of disability and death and NOTCH3 as a gene related with cardiac-cerebral vascular disease plays a vital role in IS development. However, the reports about the effect of genetic variants in NOTCH3 gene on IS are still few.Material/MethodsIn order to explore the association between NOTCH3 polymorphisms and IS, 134 patients with IS and 115 controls were enrolled in this case-control study. Polymerase chain reaction was used to do the genotyping of polymorphisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In contrast, a study based on an Austrian population without stroke showed that NOTCH3 variants were associated with the presence and progression of WMH 35 . Another study showed that only some of the NOTCH3 variants were associated with ischemic stroke in Chinese patients 36 . Therefore, most NOTCH3 variants do not seem to be associated with ischemic lesions, although there is a difference depending on race or type of polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study based on an Austrian population without stroke showed that NOTCH3 variants were associated with the presence and progression of WMH 35 . Another study showed that only some of the NOTCH3 variants were associated with ischemic stroke in Chinese patients 36 . Therefore, most NOTCH3 variants do not seem to be associated with ischemic lesions, although there is a difference depending on race or type of polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Forty percent of the studies were matched for age and gender [12,14,20,21], while 10% of the studies were matched for age and demographic area [22]. Among the included studies, the control group reported by Yuan et al [12] consisted of both population- and hospital-based controls; 80% of the cases were assessed by neuroimaging techniques except for Zhu et al [23], by a stroke specialist. In addition, 30% of the included studies deviated from HWE ( p < 0.05) [13,22,24].…”
Section: Resultsmentioning
confidence: 99%
“…There are 170 missense mutations known to cause CADASIL, in which 95% of them are identified in the NOTCH3 gene [11]. Among these mutations, NOTCH3 rs1043994, rs1044009 and rs3815188 have been associated with ischemic stroke in Chinese populations [12], but not Japanese [13,14] and Caucasian [15] populations. Indeed, the exact cause of the association of these polymorphisms with ischemic stroke risk and its subtypes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of stroke can be intensified by high blood cholesterol, tobacco addiction, obesity, high blood pressure, and diabetes mellitus. [3][4][5][6] Therefore, it is urgent to investigate the genetic variants that trigger stroke. 2 It is implied that stroke might be very likely induced by some genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is implied that stroke might be very likely induced by some genetic factors. [3][4][5][6] Therefore, it is urgent to investigate the genetic variants that trigger stroke.…”
Section: Introductionmentioning
confidence: 99%